2021
DOI: 10.1038/s41418-021-00767-2
|View full text |Cite
|
Sign up to set email alerts
|

The DJ1-Nrf2-STING axis mediates the neuroprotective effects of Withaferin A in Parkinson’s disease

Abstract: The pathogenesis of Parkinson’s disease (PD) remains unclear, and there is no disease-modifying agent for PD. Withaferin A (WA), a naturally occurring compound, has emerged as a neuroprotective agent. However, the mechanisms by which WA is neuroprotective in PD are unknown. Here we show that WA protected against loss of dopaminergic neurons, neuroinflammation, and motor deficits in MPTP-induced PD mouse models. Whole-genome deep sequencing analysis combined with Meta-analysis of human PD studies reveal that DJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 67 publications
5
20
0
Order By: Relevance
“…Experimental studies have also demonstrated that DJ-1 stimulates Nrf2 translocation to the nucleus end enhances its recruitment to the thioredoxin1 (Trx1) promoter [64]. The DJ-1, Nrf2, and STING (stimulator of interferon genes) pathways are also targeted by the anti-PD naturally occurring compound Withaferin A [65].…”
Section: Cytoprotective Activities Of Dj-1 41 Dj-1 and Reactive Oxygen Speciesmentioning
confidence: 99%
“…Experimental studies have also demonstrated that DJ-1 stimulates Nrf2 translocation to the nucleus end enhances its recruitment to the thioredoxin1 (Trx1) promoter [64]. The DJ-1, Nrf2, and STING (stimulator of interferon genes) pathways are also targeted by the anti-PD naturally occurring compound Withaferin A [65].…”
Section: Cytoprotective Activities Of Dj-1 41 Dj-1 and Reactive Oxygen Speciesmentioning
confidence: 99%
“…In this study, incubation with the two drugs indicated a decrease in Nrf2 translocation to the nucleus in agreement with previous results found in different neuronal oxidative cell models [ 24 , 35 ], which could contribute to the GPX decrease observed. The decrease in Nrf2 translocation observed in the combined model of PD and mild to moderate stress could be attributed to a decrease in Nrf2 expression [ 24 , 78 , 79 ], to Nrf2 metabolism alterations [ 80 ], or to a reduction in translocation by itself [ 81 , 82 ], induced by MPP + /MPTP; but it could also be related to the CORT effect mediated by the interaction between GR and Nrf2, owing to GR signalling blockage of Nrf2-mediated cytoprotection from oxidative distress [ 83 ]. In any case, IGF-II co-incubation prevented the Nrf2 nuclear translocation as a direct IGF-II consequence and/or trough interaction with other factors, inhibiting the GR translocation to the nucleus (see below and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parp-1, Mmp8, Hmgn1, IL-1, Nfkbid), most of which were significantly upregulated [ 109 •]. Recently, DJ-1 was shown to suppress NFkB signaling by directly interacting with its p65 subunit [ 110 ] and to mitigate inflammation mediated by the STING pathway [ 111 ]. Finally, a link between DJ-1 and regulation of gut microbiome was also described.…”
Section: Inflammation In Pdmentioning
confidence: 99%